Monomeric C-Reactive Protein and Cerebral Hemorrhage: From Bench to Bedside - Di Napoli, Mario; Slevin, Mark; Popa-Wagner, Aurel; Singh, Puneetpal; Lattanzi, Simona; Divani, Afshin A. (Frontiers in Immunology, 2018)
C-reactive protein (CRP) is an important mediator and a hallmark of the acute-phase response to inflammation. High-sensitivity assays that accurately measure levels of CRP have been recommended for use in risk assessment in ischemic stroke patients. Elevation of CRP during the acute-phase response in intracerebral hemorrhage (ICH) is also associated with the outcomes such as death and vascular complications. However, no association has been found with the increased risk of ICH. The aim of this review is to synthesize the published literature on the associations of CRP with acute ICH both as a risk biomarker and predictor of short- and long-term outcomes as well as its role as a pathogenic determinant. We believe before any clinical utility, a critical appraisal of the strengths and deficiencies of the accumulated evidence is required both to evaluate the current state of knowledge and to improve the design of future clinical studies.